Preliminary results of petroleum source rock evaluation of Mongolian Mesozoic oil shales - Erdenetsogt, Bat-Orshikh (Geological Issues, 2023)
Jurassic and Cretaceous oil shale samples, collected from northern and central Mongolian basins, have been analyzed to determine their petroleum source rock potential. The contents of total organic carbon (TOC) and total sulfur, and source rock screening data were obtained by Rock-Eval pyrolysis. Cretaceous oil shales contain up to 17.4 wt.% TOC and Hydrogen Index (HI) values range from 638-957 mg HC/g TOC. Jurassic oil shale samples have similar TOC contents, ranging from 10.7 to 17.3 wt.%. HI values of Jurassic Tsagaan-Ovoo oil shale vary between 270-313 mg HC/g TOC. Average Tmax values of Cretaceous and Jurassic samples are 4370C and 4230C, respectively. This observed data indicates that both Jurassic and Cretaceous oil shales are excellent source rock. Cretaceous oil shales contain type I kerogen (highly oil prone), while Jurassic Tsagaan-Ovoo oil shale has mixed type II/III kerogen (mixed oil and gas prone). Based on Tmax and Production Index values, both Jurassic and Cretaceous oil shales are immature. Overall, the result of this study contributes organic geochemistry database of Mongolian oil shale and encourages source rock potential of both Jurassic and Cretaceous oil shale.